State of Art on Steel Composite Slab Systems - Sutiman, Nur Adidah; Majid, M A; Jaini, Z M; A S Roslan, (Recent Trends in Civil Engineering and Built Environment, 2020)
The shift transition in the construction industry from conventional technology to Industrial Building System (IBS) must be looking at as an approachable strategy that adopts the newest and current technology. The composite structure in construction runs the method of using binary materials together to use each element for the best advantage that is obtainable by underlining the limitation of the conventional construction system. Over the past few decades, the experimental, theoretical and numerical studies have investigated the performance of steel composite slabs with or without infill materials. The literature references are carefully chosen and reviewed in this paper which focused on the steel composite slab system that applied through various types of loading such as vertical, impact, shrinkage and gravity, and water leakage. Thus, all previous research was remarked on and reported in tabular form.